2007
DOI: 10.1063/1.2760140
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional photoluminescence upconversion from PbS quantum dots

Abstract: The authors report a type of photoluminescence upconversion that is directly attributable to the strong quantum confinement of charge carriers in PbS nanocrystals and does not involve the usual mechanism of thermally populated intermediate states. Absorption, emission, and excitation spectroscopy, combined with a simple spectral model, reveals that the upconversion process is consistent with single-photon absorption by an extremely broad single nanocrystal absorption line. This type of upconversion is a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…The observed continuity of the PL signal intensity between the Stokes and the anti‐Stokes side of the spectra means that the anti‐Stokes process is as efficient as the Stokes one. This is similar to observations made on II–VI and III–V quantum dots and bulk GaN ASPL …”
Section: Resultssupporting
confidence: 91%
“…The observed continuity of the PL signal intensity between the Stokes and the anti‐Stokes side of the spectra means that the anti‐Stokes process is as efficient as the Stokes one. This is similar to observations made on II–VI and III–V quantum dots and bulk GaN ASPL …”
Section: Resultssupporting
confidence: 91%
“…4a, λ exc > 590 nm. A similar observation was reported recently for PbS QDs 25. The gradual change in the band shape suggests that the physical process involved in the QD emission is the same throughout the whole range of excitation energies.…”
Section: Phonon‐assisted Anti‐stokes Photoluminescence In Nanocrystsupporting
confidence: 88%
“…However, it happens that, most likely, the bare exciton level structure described above is not directly related to the PL up‐conversion effect. Experimentally, the blue (anti‐Stokes) shift between the ASPL peak and E abs does not significantly depend upon the QD size when the excitation photon energy is chosen proportionally to the absorption peak energy (which depends upon the size) 17–26. This is at variance with the strong size dependence of Δ E .…”
Section: Phonon‐assisted Anti‐stokes Photoluminescence In Nanocrystmentioning
confidence: 84%
See 1 more Smart Citation
“…There are some typical schemes, e.g., those based on phonon-assisted processes [17][18][19][20], and on multiphoton processes [21][22][23]. Recently, Fernée et al reported that the up-conversion range is greatly widened by an unusually-large dephasing rate in a colloidal solution of quantum dots [24]. The up-conversion in the present work is essentially distinguished from the previous ones in that it is the PL from the exciton-light coupled state with a higher exciton-light coupled mode.…”
mentioning
confidence: 99%